SURVEI DAN PEMETAAN STATUS FOSFAT LAHAN SAWAH PADA DAERAH IRIGASI BAHAL GAJAH/TIGA BOLON KECAMATAN SIDAMANIK KABUPATEN SIMALUNGUN - Meilissa Damayanti Lumban Gaol; Supriadi Supriadi; Mariani Sembiring (Universitas Sumatera Utara, 2013)
Survey and mapping phosphorus status on irrigated rice field at Bahal Gajah and Tiga Bolonvillage in Sidamanik Subdistrict. This research purpose to make a map phosphate status on wet ricefield in irrigation area Bahal Gajah/Tiga Bolon. The research start to do on May until December2012. Method of sample take use free grid survey method with semi detail survey scale. Result ofanalysis process using regreation method, with Geografis Information System (GIS) program.Parameter that analysis in laboratory is phosphate available and phosphate total. The result ofresearch showed that phosphate available divided by 3 status such as; medium (6,087 ha), high(136,005 ha), and highest (286,101 ha). Phosphate total divided by 3 status such as; medium(48,393 ha), high (109,445 ha), and highest (269,263 ha).Key words: mapping, phosphorus